Effect of Current on Mechanical Properties and Microstructure of Aluminum 6061 with Gas Tungsten Arc Welding Process - Tarmizi, Tarmizi; Sianturi, Kevin Daniel; Irfan, Irfan (Department of Naval Architecture - Diponegoro University, 2020)
Aluminum 6061 is an aluminum alloy that is widely used in various industrial fields, which heat treatable. However, it can be joined using a welding process. Aluminum joining using the Gas Tungsten Arc Welding (GTAW) process has become the option to produce good quality joints. This research aims to get optimum welding parameters by knowing the mechanical properties and microstructure of the welding results. The GTAW process uses a 25-volt voltage, Argon protective gas flow rate of 15 liters per minute with filler rod ER 5356 with 2.4 mm diameter and electrodes tungsten 2.4 mm in diameter. This process uses a single V butt joint and groove angle of 60Â° with variations in the current of 100, 110 and 120 A. The results indicate that specimens with a variety of current of 110 A give better results in the absence of defects, have a tensile strength of 152 MPa, and get a hardness value of 87.55 HV, which is the highest compared to the other two specimens. Whereas specimens with the current variation of 100 and 120 A have defects in the weld area. The optimum parameters of the 6061 aluminum GTAW process with a thickness of 6 mm using a current of 110 A bring on better outcomes and mechanical properties than the use of currents of 100 and 120 A.